Group Wage Curves - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2000)
Using panel data on U.S. MSAs, this paper estimates how a typical MSA's wages of different demographic groups, and prices, are affected by overall MSA unemployment, the distribution of unemployment among different groups, and national prices and wages. MSA unemployment has strong effects on MSA wages and prices, but the distribution of unemployment among different groups has weak effects on wages and prices. Using these estimates, simulations show that targeting high-unemployment groups for unemployment reductions will not reduce wage or price inflation pressures. The estimates also show that the effects of MSA unemployment on prices and disadvantaged groups' wages are greater (in absolute value) at lower unemployment rates. As a result, simulations using these estimates suggest that national unemployment can be reduced with less inflationary pressures by targeting unemployment reductions at MSAs with high unemployment.
Additional information: Portions of this paper are incorporated into Appendix 9 of Timothy J. Bartik. 2001. Jobs for the Poor: Can labor Demand Policies Help? New York: Russell Sage Foundation.
Keywords: J0; J3; I3; 330; wages; MSA; unemployment; demographics; inflation; Bartik